Communication Strategy of Professional Investigators and Safeguards (Propam) in Interrogating Police Problems in the Police Medan city - Kholil, Syukur; Sikumbang, Ahmad Thamrin; Amin, Afriadi (Budapest International Research and Critics University, 2020)
This research discusses; 1) cases of violations committed by members of the Indonesian National Police in Medan District Police 2) the communication strategy of Propam investigators in interrogating violations committed and; 3) the effectiveness of the communication strategy applied. Using qualitative research, data is collected through observation, in-depth interviews, and document studies. Data were analyzed using Miles and Huberman analysis. The results of the study revealed that during 2018 there were 116 cases of violations committed by members of the Indonesian National Police in the Poltabes area of Medan. To uncover the motives of the violation cases, Propam investigators use two communication strategies, namely persuasive communication and human communication. Two strategies are used, which are effective in uncovering the motives of cases of violations committed by members of the National Police in the Polrestabes area of Medan.